Viabilitas neutrofil yangdiinkubasi dalamekstrakrimpangtemulawak(Curcuma xanthorrhiza ) dan dipapar dengan Streptococcus mutans (Viability of neutrophil incubated in temulawak rhizome extract (Curcuma xanthorrhiza) and exposed by Streptococcus mutans) - Ika Wahyu Purnamasari; Pudji Astuti; Tantin Ermawati (DiscoverSys Inc., 2014)
Streptococcus mutans are bacteria that have important role in caries development. When caries lesion is developing, itmay invade to deeper tissues such as dental pulp and initiate cellular defenses such as neutrophil. Neutrophil is type ofleukocytes which are important in phagocytosis process. If neutrophil fails in phagocytosis, neutrophil will be lysis andcause viability of neutrophil unprotected. Temulawak rhizome extract is predicted to increase viability of neutrophilbecause it contains curcuminoids, volatile oil, saponin, flavonoid, and tannin. This research aimed of this research wasto determine the viability of neutrophil exposed by S.mutans and incubated in temulawak rhizomes extract 2.5%, 5%,7.5%,10%, and 20%. Twenty four samples were divided into 6 groups, consisting of negative control, temulawak rhizomeextract 2.5%, 5%, 7.5%, 10%, and 20%. The viability of neutrophil was observed under an inverted microscope usingtrypan blue staining. This study concluded that temulawak rhizome extract 2.5%, 5%, 7.5%, and 10% could increaseviability of neutrophil exposed by S.mutans. Temulawak rhizome extract 5% has the effective concentration to increase viability of neutrophil.